Advanced Solutions of Transport Systems for Growing Mobility 14th Scientific and Technical Conference "Transport Systems. Theory & Practice 2017" Selected Papers (Advances in Intelligent Systems and Computing,, 2018)
What are the parameters that should be taken into account in an advanced simulation model designed for a transport system that promotes green travelling policies? How can the goal of modal shift be pursued through ICT solutions? Is it enough to apply only a single criterion when planning transport systems? What is the importance of information acquisition and provision in Intelligent Transport Systems? Answers to these and many other questions can be found in this publication. It also contains numerous analyses based on relevant data sets, illustrating the close relationship between ITS and the changes observed in terms of how specific means of transport are used. What proves to be particularly important for advanced transport systems is the use of environmentally friendly solutions that reduce their negative environmental impacts; accordingly, the book also addresses this aspect. With regard to the research results discussed and the selected solutions applied, the book prim arily addresses the needs of three target groups: · Scientists and researchers (ITS field) · Local authorities (responsible for transport systems at the urban and regional level) · Representatives of business (traffic strategy management) and industry (manufacturers of ITS components) Advanced Solutions of Transport Systems for Growing Mobility gathers selected papers presented at the 14th "Transport Systems. Theory and Practice" Scientific and Technical Conference, organized by the Department of Transport Systems and Traffic Engineering at the Faculty of Transport of the Silesian University of Technology. The conference was held on 18-20 September 2017 in Katowice (Poland). More details at www.TSTP.polsl.pl.